Multiplying Perspectives through Text and Time: Jamaica Kincaid's Writing of the Collective - Antonia Purk (Current Objectives of Postgraduate American Studies)
Throughout Jamaica Kincaid’s fictional works, the literary technique of narrative repetition and revision multiplies narrative perspectives both with regard to singular events as well as through generations and thereby through history, pointing back to the year 1492. This article demonstrates how Kincaid thus inscribes a multitude of perspectives into what has hitherto been largely read as autobiographical fiction and, in this way, engages collective Caribbean experience as profoundly affected by the history of colonialism and slavery.